2016
DOI: 10.1177/2333721415623495
|View full text |Cite
|
Sign up to set email alerts
|

Association of Co-Existing Impairments in Cognition and Self-Rated Vision and Hearing With Health Outcomes in Older Adults

Abstract: OBJECTIVES To assess the relationship of disability (activities of daily living (ADL) and instrumental ADL (IADL)), self-rated health (SRH), and 6-year mortality with co-existing impairments in vision (self-rated), hearing (self-rated) and/or cognition (Short Portable Mental Status Questionnaire) in older adults. METHODS The study sample was comprised of 3871 participants from the North Carolina Established Populations for Epidemiologic Studies of the Elderly study (NC EPESE). RESULTS Persons with all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 58 publications
1
33
2
Order By: Relevance
“…Although some studies have reported the independent association of vision impairment and of hearing impairment with increased mortality, we observed LE estimates to be similar for those with neither or only one impairment. Presence of similar LE at age 65 for those with or without hearing impairment, although when considering hearing impairment as time invariant, was also reported from the United Kingdom .…”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…Although some studies have reported the independent association of vision impairment and of hearing impairment with increased mortality, we observed LE estimates to be similar for those with neither or only one impairment. Presence of similar LE at age 65 for those with or without hearing impairment, although when considering hearing impairment as time invariant, was also reported from the United Kingdom .…”
Section: Discussioncontrasting
confidence: 85%
“…Despite the importance of vision and hearing in the maintenance of functional ability and quality of life among older adults, vision and hearing impairments often remain undetected or underreported or untreated . Further, the impact of these impairments, especially hearing impairment, is poorly recognized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations